The OPAL exemption decision: past, present, and future - Yafimava, K (Oxford Institute for Energy Studies, 2017)
Since the OPAL pipeline started operating, more than five years ago, Gazprom has been unable to use more than 50 per cent of its capacity – even if such was not required by third parties – due to a regulatory cap imposed by the European Commission (EC) in June 2009. In October 2016 the EC adopted a new decision which removed the cap and attempted to strike a fine balance between the interests of all parties involved: while it allows Gazprom to bid for the remaining 50 per cent of OPAL capacity, it also guarantees that third parties will have access to at least 20 per cent, as Gazprom is not allowed to outbid them for that share. The decision manifests a (belated) recognition on the part of the EC that there was no rationale, rooted in the acquis, for maintaining the OPAL cap, which has become increasingly illogical and prone to criticisms of having being imposed on political grounds. Having recognised that politicisation threatens to undermine the credibility of the EU regulatory gas framework, the EC moved back into the comfort zone of rules-based regulatory decision-making, of which the October 2016 decision is an example. Poland’s legal challenge to this decision is an attempt to move in the opposite direction and risks creating a precedent in which political objectives are allowed to override regulatory rules. As such the October 2016 decision signifies an important turning point in how Russian gas will be transported to Europe in the future. It could serve as an enabler for finding a new contractual arrangement between Gazprom and Naftogaz (with mediation from the EC) for continuing transit across Ukraine post-2019 once the existing contract expires, thus reducing the urgency for the construction of Nord Stream 2 and/or the Turkish/South Stream pipelines. However should either the decision or the arrangement with Naftogaz fail or be further delayed by legal proceedings, the opposite could be the case. In any event, the decision could serve as a guidance for future regulatory treatment of onshore extensions of any new Russian transit-diversification pipelines.